Peran Work Engagement terhadap Kepuasan Hidup pada Relawan Komunitas Involuntir - Harlyin Chandra Tio (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This study aims to examine the role of work engagement in life satisfaction among volunteers of the Involuntir community. Engagement in volunteer activities is often associated with subjective well-being; however, the dynamics of this relationship have not been fully understood, particularly in the context of young volunteers. This study employed a quantitative method with purposive sampling, involving 122 active Involuntir volunteers. The instruments used were the Utrecht Work engagement Scale (UWES-17) to measure work engagement and the Satisfaction With Life Scale (SWLS) to assess life satisfaction. Data analysis was conducted using Spearman’s rho correlation test and regression analysis due to non-normally distributed data. Descriptive analysis results indicated that volunteers’ work engagement levels were categorized as high, while life satisfaction levels were categorized as moderate. The results of the Spearman’s rho correlation test revealed a significant negative relationship between work engagement and life satisfaction (r = −0.522; p < 0.05). Furthermore, regression analysis showed that work engagement had a significant effect on life satisfaction with a negative coefficient direction (β = −0.072; p < 0.05), indicating that higher levels of work engagement were associated with lower levels of perceived life satisfaction. Additionally, the Mann–Whitney difference test results indicated no significant differences in either work engagement or life satisfaction based on gender. Overall, this study suggests that high levels of volunteer engagement need to be managed in a balanced manner, as excessive engagement may potentially reduce life satisfaction. These findings highlight the importance of sustainable volunteer engagement management in supporting the subjective well-being of young volunteers